Effects of Gaming on Children’s Brains: Depression and Social Isolation - Nguyen, Trent; Landau, Susan (Advances in Social Sciences Research Journal, 2019)
This study documents the effects of gaming on children’s brains, focusing on the negative effects of gaming, and in particular, social isolation and depression. Over the years, psychologists, parents and the general public have played a key role in advancing literature on gaming and brain development, thus enabling researchers to gain a deeper understanding of the adverse effects of excessive gaming. The main purpose of this study is to demonstrate that excessive gaming is strongly correlated with adverse effects such as social isolation and depression by reviewing various scholarly articles which clearly indicate that excessive gaming can derails a person’s efforts to make real friends by affecting their social skills and making them aggressive. In the long run, children gamers become socially isolated. This paves way for depression and other self-harming habits. The methodology section justifies why the research had to be underlined by secondary research and secondary data. Results section reports actual findings on how gaming activates pleasure circuits to a certain degree, which leads to impulsive behavior that prevent children from engaging in active social lives.